Using Technical Analysis and Settlement Analysis Together in Stocks - Çetinkaya, Reşit (Bilgicagi Education Consulting and Publishing Industry Trade Limited Company, 2025)
The purpose of this study is to predict the future direction of asset prices in the stock market using historical data and to determine the timing of market entry and exit using technical analysis data. The study covers 10 liquid non-bank stocks listed on the Istanbul Stock Exchange (BIST). The methods used for price predictions for these stocks are technical analysis and settlement analysis. Exchange analysis will be used to identify which stocks buyers are focusing on in the stock market, and technical indicators will be used on the stocks to determine the most appropriate entry and exit times. Thus, stock returns will be evaluated using technical data to predict the future direction of stock prices. In this context, it will be easy to see whether stocks are in a buy, sell, or hold position. In particular, the settlement analysis provides insights into whether there is demand for stocks from existing holders and new investors, as well as the future direction of stock prices. In this study, the connection between technical analysis signals and returns will be explored by considering changes in the settlement shares of the top five brokerage firms in stocks. In the settlement analysis, exchange data from July 2024 to August 2025 will be considered on a monthly basis. The exchange shares will be displayed for the top five brokerage firms, while the sum of the exchange shares of the dozens of brokerage firms outside this group will be shown as the “OTHERS” group. The EMA (Exponential Moving Average) was used as the technical indicator. The time periods used were the 5-day and 22-day averages. As a result, it is assumed that when technical and settlement analysis data are used together, stock returns increase for investors, thus contributing to a more robust investment strategy.